Modified Y-splitting Procedure for the Treatment of Duane Retraction Syndrome - Ayşe Gül Altıntaş; Hasan Basri Arifoğlu; Şükrü Gültekin Köklü (Türk Oftalmoloji Dergisi, 2015)
Objectives: To present the outcomes of modified lateral rectus Y-splitting combined with either unilateral or bilateral horizontal rectus recession in Duane Retraction Syndrome (DRS) with significant upshoot or downshoot. Materials and Methods: A total of 12 patients including 10 patients with Type I DRS and 2 with Type III DRS underwent modified Y-splitting surgery. Amount of additional recessions varied with the degree of preoperative deviation by intraoperative adjustable suture technique. Preoperatively 3 patients had esotropia (ET), 6 had exotropia (XT), and 3 patients had orthotropia. The mean preoperative deviation was 19.3 prism diopters (PD) (range, 18-20 PD) in ET patients and 19.2 PD (range, 16-20 PD) in XT patients. Results: Postoperatively, all patients had significant correction in horizontal deviation and aligned within 4 PD of orthotropia, and no patients exhibited abnormal head posture. Co-contraction and globe retraction were markedly reduced and abnormal ocular vertical movement disappeared or significantly decreased in all cases. No patients experienced recurrence of ocular motility disorders in the mean 26-month (range, 13-66 months) follow-up period. Conclusion: Modified Y-splitting surgery combined with co-contracting horizontal muscle recession technique seems to be a safe and effective treatment in DRS. (Turk J Ophthalmol 2015; 45: 152-155)